Estigma relacionado à hanseníase em comunidades e pessoas acometidas em território hiperendêmico do Nordeste do Brasil - Andrade, Thainá Isabel Bessa de (2022)
Leprosy is a Neglected Tropical Disease (NTD), infectious and chronic, with a slow course, with great disabling and stigmatizing potential. Its first reports date back thousands of years and the symptoms of the disease were understood as a sign of impurity and divine punishment highlighted by religious dogmas. At the beginning of the 20th century, people affected by leprosy were subjected to segregation processes marked by social exclusion, compulsory hospitalization and isolation, contributing to the sociocultural construction of the disease in the current times and resulting in strong stigma, prejudice and negative valuation. The stigma associated with the disease can also change the conception of territories and the work, religious, leisure and community activities that occur there, maintaining a persistent cycle of stigmatization. The objective of this study was to analyze the expression of stigma related to leprosy perceived by professionals/managers of health, education, the general community and people affected by the disease in the hyperendemic municipality of Floriano, Piauí. This is a cross-sectional study of an operational nature and quantitative nature, conducted in the municipality of Floriano, State of Piauí, from May to December 2019. Initially, the sociohistorical-cultural context of the stigma resulting from leprosy in the municipality was described. The study population was analyzed in terms of their sociodemographic, clinical and operational characteristics using a specific instrument. The perception of stigma was assessed through the application of the Explanatory Model Interview Catalog for the community (EMICCSS) and for affected people (EMIC-AP). For the EMIC-CSS, 30 health professionals/managers, 30 education professionals/managers and 55 community members who have never had or have leprosy were approached. For EMIC-AP, 16 people undergoing treatment for leprosy or post-discharge, with or without leprosy reaction, were approached. All data collected were consolidated and analyzed using descriptive statistics based on frequencies and measures of central tendency and dispersion. Comparisons between categorical variables were based on Pearson's chi-square test, with a confidence level of 95%. The project was submitted and approved by the Ethics and Research Committee of the Federal University of Bahia. Despite the general reduction in new cases of leprosy in the last decade, Floriano remains a municipality marked by its hyperendemicity. In addition to the persistent expression of the 11 disease, stories of discrimination against affected people are outlined, resulting in social exclusion, obstacles to early diagnosis and verification of physical sequelae due to the high disabling potential. For the EMIC-CSS, the score ranged from 0 to 28 points, with an average of 18.9 for health professionals, 15.7 for education professionals and 15.3 for the general community. There was an association of EMIC-CSS with the category of participants (p=0.016), schooling (p=0.021), monthly income (p=0.011) and participation in educational/informational activities about leprosy (p=0.049). As for EMIC-AP, scores ranged from 0 to 25 points, reaching an average of 11.4. EMIC-AP was associated with individuals with physical disability (p= 0.032). The results found show a high degree of stigma perceived in the community and its association with sociodemographic, clinical and operational variables. The usefulness of stigma scales as facilitators of their dimensioning in health, school and community environments is also highlighted as one of the strategies defined by national and international agendas to combat leprosy.